1985
DOI: 10.1136/gut.26.6.615
|View full text |Cite
|
Sign up to set email alerts
|

Pressure, volume and the pancreas.

Abstract: for eight hours, were carefully weighed and anaesthetised with 1*2 mg intraperitoneal sodium pentobarbitone, and maintained at a constant temperature of 37°C. Through a midline laparotomy wound the duodenum and bile-pancreatic duct were identified. In the rat multiple pancreatic ducts drain into a common bile-pancreatic duct which empties into the second part of the duodenum.9 10 The greater part of the bile-pancreatic duct is enveloped in pancreas but at each end there is an exposed segment 1-2 mm long allowi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

1985
1985
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 22 publications
2
10
0
Order By: Relevance
“…Calcium homeostasis is affected early during pancreatic injury since acini isolated from saline-infused animals showed evident impairment in calcium response. These results support those obtained for other authors [25][26][27] and point to the need of developing new diagnostic techniques in order to reduce the risk of causing pancreatic damage in ERCP. These approaches would be directed to reduce manipulation avoiding mechanical damage and flow obstruction in pancreatic duct.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Calcium homeostasis is affected early during pancreatic injury since acini isolated from saline-infused animals showed evident impairment in calcium response. These results support those obtained for other authors [25][26][27] and point to the need of developing new diagnostic techniques in order to reduce the risk of causing pancreatic damage in ERCP. These approaches would be directed to reduce manipulation avoiding mechanical damage and flow obstruction in pancreatic duct.…”
Section: Discussionsupporting
confidence: 91%
“…Thus, hydrostatic pressure increase could be one of several factors that can trigger the inflammatory reaction in the pancreas [24]. Moreover, infusion of saline into rat biliopancreatic duct can lead to pancreatic and pulmonary damage [25,26], hyperamylasemia, inflammatory cell infiltration, and trypsin activation in the pancreas [27].…”
Section: Introductionmentioning
confidence: 99%
“…1. Previous studies have reported that the average intrapancreatic duct pressure in patients with CP is 33.1 cmH 2O (6), and the pancreatic duct ruptures at a pressure of 50 cmH2O in rats (4). Therefore, the free end of the pancreatic cannula was raised 5 cm each day from 25 to 35 cm but not above 35 cm to prevent acute pancreatic damage.…”
Section: Methodsmentioning
confidence: 97%
“…Both chemical and pressure effects of infusion were suggested to play a major role in the pathogenesis of pancreatitis in perfusion models 48,49. In both chemical- and pressure-induced pancreatitis, destruction of the pancreatic duct mucosal barrier is the key event.…”
Section: Models Of Acute Pancreatitismentioning
confidence: 99%
“…Several experiments were performed to assess maximal pancreatic duct pressure before rupture of the duct epithelium causing increased and uncontrolled severity of acute pancreatitis. Data are conflicting, with rupture pressures varying from 15 to 82 mmHg 48,49,51,52. A maximum infusion pressure of 30 to 50 mmHg is currently accepted for rat models.…”
Section: Models Of Acute Pancreatitismentioning
confidence: 99%